Case study of social marketing implementation in covid-19 promotion media and public knowledge of covid-19 in Jayapura city - Zainuri, Agus; Putra, Mifta Fariz Prima; Irap, S. Piter; Indrayani, Ervina (Jurnal Konseling dan Pendidikan, 2024)
This research is based on the critical role of social marketing in raising awareness and promoting healthy behaviors during the COVID-19 pandemic, particularly in Jayapura City, where challenges persist in disseminating effective information and influencing public behavior regarding health protocol adherence. The study aims to analyze the implementation of social marketing through promotional media, such as posters and health protocols displayed in public areas, in enhancing knowledge and influencing behavioral changes among the residents of Jayapura City in COVID-19 prevention. A qualitative case study method was used to evaluate the implementation of social marketing in COVID-19 promotional media and its impact on public knowledge in Jayapura City. Data collection was conducted through semi-structured interviews with respondents from diverse social backgrounds, as well as direct observation of promotional media distributed throughout the city. The findings reveal that while promotional media, such as COVID-19 posters and health protocols displayed in public areas, succeeded in improving the public's basic understanding of the importance of health protocols, there were significant barriers to the consistent application of such behaviors. Factors such as limited access to information, a lack of in-depth understanding, and social resistance to behavioral changes posed considerable challenges to enhancing the effectiveness of the campaign. The research also found that while the campaign positively impacted awareness levels, a more integrated and contextual approach is needed to achieve comprehensive behavioral change among the community.